Author Correction: Induced unconventional superconductivity on the surface states of Bi2Te3 topological insulator - Sophie Charpentier (Nature Portfolio, 2018)
The original version of this Article contained an error in Fig. 6b. In the top scattering process, while the positioning of both arrows was correct, the colours were switched: the first arrow was red and the second arrow was blue, rather than the correct order of blue then red.